Systems biology of the cell cycle - Novak, Bela (Henry Stewart Talks, 2014)
Control of cell cycle progression in eukaryotes by a network of universal protein interactions, This dynamic system oscillates once per cell cycle, Oscillation ceases when genomic integrity is in jeopardy, The negative feedback loop by which Cdk1/CycB promotes CycB degradation via activation of APC/C, Bistable (‘toggle’) switches are also important design principles of eukaryotic cell cycle control network, The cell cycle
Reviewed at 2022/01/23